PHENOTYPIC VARIATION OF FRUITS, SEED GERMINATION AND EARLY GROWTH OF BLIGHA SAPIDA K.D. KONIG IN SELECTED LOCATIONS OF ONDO STATE, NIGERIA - Johnson Adeyinka OLUSOLA; Olubukola Victoria OYERINDE; Faithful Olayinka IYAGIN; Oluronke Olubunmi SOBOLA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tropical forest contains many plant species that are cultivated for food but they are neglected and underutilized despite their importance. This study examined phenotypic variation of trees and fruits of Blighia sapida conducted at (Akure, Owo and Akoko) within Ondo State, Nigeria. Five healthy trees were selected and twenty (20) matured fruits were collected from each tree. Data collected from selected trees were tree growth, fruits and seeds. The result indicates that highest tree height 14.0 m was recorded in Akoko and 8. 00 m was found in Akure B. sapida trees but tree dbh shows that 19. 46 cm, 19.44 cm and 18.34 cm were found for Owo, Akoko and Akure trees while 8. 48 m, 7. 60 m and 7. 12 m were for crown diameter found for Akure, Owo and Akoko tree respectively. But for seed parameter it shows that 1.85, 1. 75 and 1.71 were found for the seed no/fruit for Akoko, Owo and Akure, and 2.14, 2. 03 and 1.99 cm for seed length for Akoko, Akure and Owo respectively. Seed breadth ranged from 1. 67 cm – 1.81 cm and seed weight ranged from 8. 19g -7.61g. Fruit parameters show that highest fruit length was found in Akoko with 4. 90 cm while Owo fruits had least with 3.78 cm, for fruit breadth Akoko had the highest value of 4.08 cm Owo had the last value of 3. 37 cm but for fruit weight Akoko had the highest with 42. 33 g while Akure had the least weight of 42.20 g respectively. The variation in fruit and seed of B. sapida could be due to climatic, edaphic factors and cultural factors.